2007
DOI: 10.1186/1471-2407-7-228
|View full text |Cite
|
Sign up to set email alerts
|

Meat, vegetables and genetic polymorphisms and the risk of colorectal carcinomas and adenomas

Abstract: BackgroundThe risk of sporadic colorectal cancer (CRC) is mainly associated with lifestyle factors, particularly dietary factors. Diets high in red meat and fat and low in fruit and vegetables are associated with an increased risk of CRC. The dietary effects may be modulated by genetic polymorphisms in biotransformation genes. In this study we aimed to evaluate the role of dietary factors in combination with genetic factors in the different stages of colorectal carcinogenesis in a Norwegian population.MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 48 publications
3
42
0
1
Order By: Relevance
“…The overall genotype distribution is not different from data on Caucasians with colorectal carcinoma (Ile/Ile 47, Ile/Val 46 and Val/Val 6%) (Skjelbred et al, 2007). A similar distribution is also found in CAPIRI patients, but not in those receiving CAP.…”
Section: Discussionsupporting
confidence: 53%
“…The overall genotype distribution is not different from data on Caucasians with colorectal carcinoma (Ile/Ile 47, Ile/Val 46 and Val/Val 6%) (Skjelbred et al, 2007). A similar distribution is also found in CAPIRI patients, but not in those receiving CAP.…”
Section: Discussionsupporting
confidence: 53%
“…Previous epidemiological studies have indicated that red meat consumption and smoking were associated with increased CRA risk; in contrast, fruit and vegetable intake were associated with decreased CRA risk [6,7], but the results were inconsistent from country to country [6], which indicated that polymorphisms in genes encoding the enzymes involved in the metabolism of dietary chemicals may be responsible for the differences [4,8]. Phase I metabolic enzymes including cytochrome P450 1A1 (CYP1A1), CYP1A2 and microsomal epoxidehydrolase 1 (EPHX1) can catalyze the hydrolysis of arene, alkene and aliphatic epoxides to less reactive and more watersoluble dihydrodiols but catalyze the polycyclic aromatic hydrocarbons, which are mainly from cooked meat or cigarette to a more carcinogenic form [9,10].…”
Section: Introductionmentioning
confidence: 67%
“…In contrast, a significant association of GSTM1 null genotype carriers and an increased CRC risk was described in a recent study. Some case-control studies provide evidence that the presence of GSTM1 in conjuction with low intake of cruciferous vegetables is an important risk factor for CRC or pre-cancerous lesions [18,19].…”
Section: Discussionmentioning
confidence: 99%